Stroke in Pregnancy - Sells, Christina Mijalski; Feske, Steven K. (Seminars in Neurology, 2017)
Pregnancy and the postpartum period confer an increased risk of stroke. The risk appears to be increased for all strokes during the puerperium and for hemorrhagic strokes during pregnancy. During pregnancy, physiologic systems are under increased stress to accommodate the growing fetus, which results in substantial hemodynamic, cardiovascular, hematologic, immunologic, and structural connective tissue changes that account for much of this increased risk. In addition, preeclampsia–eclampsia has major effects on the vascular system, and this disorder, unique to pregnancy, is another major contributor to this risk. The common independent vascular risk factors for stroke, such as hypertension, diabetes, hyperlipidemia, and smoking, may also be present to contribute to the risks conferred by pregnancy. Though uncommon, stroke during pregnancy and in the postpartum period causes substantial morbidity and mortality in affected women, and it poses a significant risk to the fetus. This review will discuss the epidemiology of pregnancy-associated stroke, specific risk factors and mechanisms, clinical presentation and management, and future directions.
Keywords: stroke; cerebrovascular disease; pregnancy; peripartum; puerperium; preeclampsia–eclampsia; cerebral venous thrombosis